PENGARUH UKURAN PERUSAHAAN, TINGKAT PERTUMBUHAN, PROFITABILITAS, RISIKO BISNIS, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - Dimabherti Ardian Nugroho, 14.05.52.0294; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2018)
The purpose of this research are for examine and analyze the effect of firm size, growth, profitability, business risk and asset tangibility to capital structure at manufacture companies listed on the BEI 2014-2017. The sampling technique in this research use purposive sampling. The sample in this study using 184 data from 46 companies manufacture sector listed on BEI year 2014-2017. Analysis method is multiple linear regression. The result are : the assets tangibility, firm size and growth have a positive effect on the capital structure, Profitability negatively affect the capital structure, and business risk are not significant with the capital structure. Keywords :fsize, grow, prof, brisk, tangb, lev